Analyzing Consumer Attitudes Toward Product Attributes of Kasturi Orange Syrup Using the Fishbein Multi-Attribute Model: A Case Study of Kasturea (International Journal of Economics and Management Research, 2026)
The growing trend toward healthier lifestyles has influenced consumer preferences for natural beverage products, including locally produced citrus-based syrups. This study aims to analyze consumer attitudes toward Kasturea’s Kasturi (calamansi) orange syrup and to identify the attributes that most influence overall evaluation. A quantitative approach was employed using structured questionnaires distributed to 100 consumers selected through purposive sampling. The Fishbein Multi-Attribute Model (Ao = Σ bi × ei) was applied to measure overall consumer attitudes by combining belief strength and attribute importance across ten product attributes. The results indicate that consumers generally hold a positive attitude toward the product, reflected in a total attitude score of 187. Shelf life, natural ingredients, and price contributed most significantly to the overall attitude, indicating strong functional and economic positioning. However, a gap between the high importance and moderate belief levels of taste and aroma suggests the need for sensory quality improvement. The findings confirm the usefulness of the Fishbein Model in evaluating consumer attitudes and provide strategic insights for product development and marketing improvement.